Analysis of Customer Loyalty Through Service Quality, Price, Brand Image, and Customer Satisfaction as Mediators at PT. Angkasa Pura Logistik at I Gusti Ngurah Rai Airport Cargo Terminal - Faathirrajaf Trisnawan; Adi Nurmahdi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the factors that affect Customer Loyalty at the Cargo Terminal of PT Angkasa Pura Logistik I Gusti Ngurah Rai Airport Denpasar by using service quality, price and brand image as research variables through customer satisfaction. The population of this study is customers from PT. Angkasa Pura Logistics with a sample of 164 respondents. The results of this study show that of the four variables, including price to customer loyalty through customer satisfaction as mediation, brand image to customer loyalty through customer satisfaction as mediation, price to customer loyalty and brand image to customer loyalty which have a positive and significant effect. Meanwhile, the quality of service to customer loyalty through customer satisfaction as a mediator, the quality of service to customer loyalty and the brand image to customer loyalty have no positive and significant effect.